If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x = -2x + 49 Reorder the terms: 4x = 49 + -2x Solving 4x = 49 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 4x + 2x = 49 + -2x + 2x Combine like terms: 4x + 2x = 6x 6x = 49 + -2x + 2x Combine like terms: -2x + 2x = 0 6x = 49 + 0 6x = 49 Divide each side by '6'. x = 8.166666667 Simplifying x = 8.166666667
| 2q+905=439 | | F(x+8)=9x-4 | | (3k)^4/3 | | 10x-11=5x-2 | | 53-13=-10x+6x | | 507=(x*3x)/2 | | (-6)-3y=3 | | 9p-8=12+5p | | (3k)^4/5 | | 2x+3x=-8-12 | | F(4)=9x-4 | | 9R-18=26+R | | 16x^3+12x^2+8x= | | 9x(x-2)=(x+2) | | 5b-10-3b= | | x-3(-1)=3 | | (27b^6)^4/3 | | (2x+16)=(x+14) | | (n^5)^4/5 | | 1.03x=113740 | | 4x+18=2x+54 | | 103x=113740 | | 7/11x=2 | | 3x+24y=12 | | X^2-8x=32 | | 28-2x=13-7x | | 3+30x=15x+21 | | 13+3(3x+8)=8-x | | 2ln(3x-2)+2=0 | | 6z+z=z-4 | | .50x+0.15(30)=27.5 | | 11-14x+28+30x=4x-12+23+6x |